EFFECTIVENESS OF YOGA THERAPY EDUCATION ON KNOWLEDGE AND ATTITUDES OF T2DM PATIENTS IN TAKALAR REGENCY - Suardi, Suardi; Ernawati, Ernawati; Oktaviana, Dina; Alwi, Alwi; Patmawati, Patmawati; Dewiyanti, Dewiyanti; Wahyudin, Wahyudin; Zainuddin, Zainuddin; Ilham, Rosmin; Thalib, Abdul (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Background: Diabetes mellitus is a chronic disease characterized by increased blood sugar levels (hyperglycemia) and glucose intolerance caused by the pancreas not producing enough insulin or the body being unable to use the insulin produced effectively. Objective: to determine the effectiveness of yoga therapy education on knowledge and attitudes in T2DM patients in Takalar Regency. Method: This research uses an experimental approach with a one-group pre-post test design. The number of respondents was 30 using the Accidental Sampling sampling method. The statistical test used is the paired sample test with ρ<0.05. Results: In this study, pre-intervention knowledge results were obtained with a mean of 5.47, and mean post-intervention knowledge increased to 8.47 with a value of ρ=0.001, while pre-intervention attitudes had a mean of 20.20, while post-intervention attitudes the mean increased to 26.83, with a value of ρ=0.001. Conclusion: there is an influence of yoga therapy education on the knowledge and attitudes of T2DM patients in Takalar Regency.